Stock predictions and virtual population analysis of three invasive fish species in the Shatt Al-Arab River, Iraq - Mohamed, Abdul-Razak (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Carassius auratus, Oreochromis aureus and Coptodon zillii are invaded fish in the Iraqi waters and are well established and considered one of the dominant species in different natural waters of the country. The stock predictions and virtual population analysis of these species in the Shatt Al-Arab River were studied from November 2015 to October 2016 using the FiSAT II software. A total of 1,511 individuals of C. auratus, 1,353 O. aureus and 1,285 C. zillii were measured to analyze the length-frequencies. The growth was positive allometric for all species. The asymptotic length (L?) was computed as 21.2, 27.0 and 29.3 cm for C. auratus, O. aureus and C. zillii, respectively. The rates of total mortality (Z), fishing (F), natural (M) and exploitation (E) for C. auratus were 2.69, 1.09, 1.60 and 0.59, O. aureus 2.49, 1.08, 1.41 and 0.57 and C. zillii 1.51, 0.84, 0.68 and 0.45, respectively. The present exploitation rates (E) for O. aureus and C. zillii are lower than the biological target reference points for both species expressing a case of under-exploitation of both species, while C. auratus was operating nearby the exploited situation. Virtual population analysis (VPA) showed that the maximum fishing mortality for the three species occurred in the mid-lengths, with maximum values at the length of 16 cm for C. auratus and O. aureus and 15 cm for C. zillii. Therefore, the present study proposes that more yields can get through increasing the fishing activities on these invasive species, such as increasing the number of fishing boats and decreasing the mesh size to decline their abundances in the long term.